Donn Piatt : Gadfly of the Gilded Age - Bridges, Peter, 1932- (Book collections on Project MUSE., 2012)
"The life of a celebrated diplomat and editor whose opinions helped to shape views on the national agenda. Born in 1819 in Cincinnati, Donn Piatt died in 1891 at the Piatt Castles that still stand in western Ohio. He was a diplomat, historian, journalist, judge, lawyer, legislator, lobbyist, novelist, playwright, poet, and politician - and a well-known humorist, once called on to replace Mark Twain when Twain's humor failed him. A staunch opponent of slavery, Piatt campaigned in 1860 for Abraham Lincoln, who briefly took a liking to him but found him too outspoken and later cursed him when, as a Union officer, Piatt recruited slaves in Maryland."--Project Muse.